Pentingnya Pelayanan Gembala Sidang Dalam Menjangkau Jiwa Di GPK Di Nek Kompong Desa Andeng Kecamatan Sengah Temila Kabupaten Landak - Stepanus Akian; Marthen Mau (Jurnal DIKMAS, 2023)
Reaching souls in GPKdI Nek Kompong, Andeng Village in conjunction with reaching out to souls in GKSI Moria Empaong-Nala Congregation is very much needed by pastors who are serious and sincere in their ministry. The ministry of a pastor to reach the soul is a very important act today. The purpose of reaching out to souls is to save lost souls to live like Christ. In order for the pastor to be more enthusiastic in reaching lost souls, prayers and fasting are required to be carried out by the pastor, the church assembly, and all members of the Nek Kompong GPKdI, Andeng village and in the GKSI Moria Empaong-Nala Congregation. This study uses a qualitative methodology with a data processing approach of observation, interviews, and documentation. The results of the study showed that some members of the GPKdI Nek Kompong and GKSI Moria Empaong-Nala congregations already had an awareness of fellowship with God in places of worship and other spiritual fellowship carried out in the congregation. The conclusion is that pastors must be loyal in reaching out to souls in GPKdI Nek Kompong and GKSI Moria Empaong-Nala Congregation continuously and even ministry to reach souls must also be carried out by pastors/congregations in all interdenominational churches, both in Indonesia and elsewhere world.